Hedonic wage equilibrium: Theory, evidence and policy - Thomas J. Kniesner; John D. Leeth (Institute for the Study of Labor (IZA), 2010)
We examine theoretically and empirically the properties of the equilibrium wage function and its implications for policy. Our emphasis is on how the researcher approaches economic and policy questions when there is labor market heterogeneity leading to a set of wages. We focus on the application where hedonic models have been most successful at clarifying policy relevant outcomes and policy effects, that of the wage premia for fatal injury risk. Estimates of the overall hedonic locus we discuss imply the so-called value of a statistical life (VSL) that is useful as the benefit value in a cost-effectiveness calculation of government programs to enhance personal safety. Additional econometric results described are the multiple dimensions of heterogeneity in VSL, including by age and consumption plans, the latent trait that affects wages and job safety setting choice, and family income. Simulations of hedonic market outcomes are also valuable research tools. To demonstrate the additional usefulness of giving detail to the underlying structure we not only develop the issue of welfare comparisons theoretically but also illustrate how numerical simulations of the underlying structure can also be informative. Using a reasonable set of primitives we see that job safety regulations are much more limited in their potential for improving workplace safety efficiently compared to mandatory injury insurance with experience rated premiums. The simulations reveal how regulations incent some workers to take more dangerous jobs, while workers' compensation insurance does not (or less so).
Keywords: J2; J3; 330; hedonic labor market equilibrium; job safety; VSL; panel data; quantile regression; OSHA; workers' compensation insurance; Lohntheorie; Lohn; Hedonischer Preisindex; Wert des Lebens; Arbeitsunfall; Risiko; Arbeitsschutz; Arbeitsmarkttheorie; Theorie; Schätzung; USA